2023
DOI: 10.1039/d2su00046f
|View full text |Cite
|
Sign up to set email alerts
|

Birch fractionation in γ-valerolactone with the emphasis on pulp properties: prehydrolysis, acid-catalyzed, and alkaline-catalyzed concept

Abstract: Acid-catalyzed organosolv GVL pulping can yield high-purity dissolving pulp from birch with qualities comparable to commercial acid sulfite dissolving pulp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Recent research indicates that biobased solvents, including glycerol ethers, ,, alkanediols, dihydrolevoglucosenone (Cyrene), γ-valerolactone (GVL), and ethyl lactate, can serve as efficient hydrotropes to increase the aqueous solubility of hydrophobic compounds. Moity et al showed that monoglycerol ethers improve the solubility of hydrophobic dyes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research indicates that biobased solvents, including glycerol ethers, ,, alkanediols, dihydrolevoglucosenone (Cyrene), γ-valerolactone (GVL), and ethyl lactate, can serve as efficient hydrotropes to increase the aqueous solubility of hydrophobic compounds. Moity et al showed that monoglycerol ethers improve the solubility of hydrophobic dyes.…”
Section: Introductionmentioning
confidence: 99%
“…γ-valerolactone, …). 207,208 The ability of different organic solvents to solubilize lignin is commonly described using the Hildebrand solubility parameter ( δ ), defined according to eqn (2).wherein Δ H̃ is the molar heat of vaporization of the solvent (J mol −1 ), R is the ideal gas constant (J mol −1 K −1 ), T is the temperature (K), and Ṽ is the molar volume of the solvent (m 3 mol −1 ). For optimal solvency, the Hildebrand solubility parameter of the solvent should match that of the solute, which, in the case of lignin, is about 23.5 MPa 1/2 .…”
Section: Lignocellulose Pretreatment As a Source Of Ligninmentioning
confidence: 99%
“…g-valerolactone, .). 207,208 The ability of different organic solvents to solubilize lignin is commonly described using the Hildebrand solubility parameter (d), dened according to eqn (2).…”
Section: mentioning
confidence: 99%
“…Alternatively, γvalerolactone (GVL) with cheap and non-toxic characteristics is considered as a promising candidate for the upgrading of paper-grade pulp (Fang and Sixta 2015). GVL is a biomassbased platform compound that can be acquired by the conversion of cellulose and hemicellulose (Giselle et al 2023;Granatier et al 2023a;Marianna et al 2023). Due to its non-toxicity, biodegradability, recyclability, and eco-friendliness, GVL has become an ideal solvent in the synthesis of some chemicals (Climent et al 2011;Sorokina et al 2022).…”
Section: Introductionmentioning
confidence: 99%